Loop-mediated Isothermal Amplification and nested PCR of the Internal Transcribed Spacer (ITS) for Histoplasma capsulatum detection - Zatti, Matheus da Silva (PLoS Negl Trop Dis, 2019)
BACKGROUND: Histoplasmosis is a neglected disease that affects mainly immunocompromised patients, presenting a progressive dissemination pattern and a high mortality rate, mainly due to delayed diagnosis, caused by slow fungal growth in culture. Therefore, a fast, suitable and cost-effective assay is required for the diagnosis of histoplasmosis in resource-limited laboratories. This study aimed to develop and evaluate two new molecular approaches for a more cost-effective diagnosis of histoplasmosis. METHODOLOGY: Seeking a fast, suitable, sensitive, specific and low-cost molecular detection technique, we developed a new Loop-mediated Isothermal Amplification (LAMP) assay and nested PCR, both targeting the Internal Transcribed Spacer (ITS) multicopy region of Histoplasma capsulatum. The sensitivity was evaluated using 26 bone marrow and 1 whole blood specimens from patients suspected to have histoplasmosis and 5 whole blood samples from healthy subjects. All specimens were evaluated in culture, as a reference standard test, and Hcp100 nPCR, as a molecular reference test. A heparin-containing whole blood sample from a heathy subject was spiked with H. capsulatum cells and directly assayed with no previous DNA extraction. RESULTS: Both assays were able to detect down to 1 fg/μL of H. capsulatum DNA, and ITS LAMP results could also be revealed to the naked-eye by adding SYBR green to the reaction tube. In addition, both assays were able to detect all clades of Histoplasma capsulatum cryptic species complex. No cross-reaction with other fungal pathogens was presented. In comparison with Hcp100 nPCR, both assays reached 83% sensitivity and 92% specificity. Furthermore, ITS LAMP assay showed no need for DNA extraction, since it could be directly applied to crude whole blood specimens, with a limit of detection of 10 yeasts/μL. CONCLUSION: ITS LAMP and nPCR assays have the potential to be used in conjunction with culture for early diagnosis of progressive disseminated histoplasmosis, allowing earlier, appropriate treatment of the patient. The possibility of applying ITS LAMP, as a direct assay, with no DNA extraction and purification steps, makes it suitable for resource-limited laboratories. However, more studies are necessary to validate ITS LAMP and nPCR as direct assay in other types of clinical specimens.